Patterns of recombination detected in the global metapopulation of begomoviruses based on DNA-A sequences - Morais Júnior, Ivair José (2020)
The global meta-population of begomoviruses (single-stranded [ss]DNA plant viruses of the genus Begomovirus) is structured in two large subpopulations that can be further subdivided into eight smaller ones due to geographical barriers and host range. Recombination is one of the evolutionary mechanisms that most contribute to the diversification of viral populations, and it is believed that a conserved pattern of breakpoints distribution exists in ssDNA virus genomes. However, the genetic isolation might give rise to unique recombination patterns within each virus subpopulation. In this context, the aim of this study was to determine the genetic structure of global meta-population of begomoviruses and to compare the recombination patterns from each subpopulation. DNA-A sequences of begomoviruses available from GenBank were analysed using discriminant analysis of principal components (DAPC). Detection of recombination was performed using RDP4 and validated by evidence of non-bifurcated diversification by the Neighbour-Net method. The begomovirus subpopulations were designated as: (i) EACM- and SACM-like viruses, (ii) ACM-like viruses, (iii) sweepoviruses, (iv) Meso- and Latin Americas, (v) America and Middle East, (vi) TYLC-like viruses, (vii) isolates from various native species from Far East and Indian subcontinent and (viii) isolated from various Asian and African countries. The recombination patterns showed differences according to the subpopulation analysed, suggesting that, contrary to what has been postulated over the last decade, there is no widely conserved pattern in begomoviruses genomes.